Contrast-Enhanced MR Imaging of Cerebral Fat Embolism: Case Report and Review of the Literature - Simon, Andrew D.; Ulmer, John L.; Strottmann, James M. (American Journal of Neuroradiology, 2003)
Summary: We report a case of cerebral fat embolism (CFE) that was imaged with T2- and T2*-weighted, fluid-attenuated inversion recovery, and contrast-enhanced T1-weighted images. Multiple white matter lesions demonstrated contrast enhancement, with little evidence of hemorrhage. The patient regained complete neurologic function. CFE can cause capillary inflammation and breakdown of the blood-brain barrier, without associated hemorrhage or permanent neurologic deficit. In this case, both contrast-enhanced T1-weighted and gradient-echo T2*-weighted images were important in diagnosing CFE and in determining the severity of the patient’s condition.